Factors associated with prehospital delay in patients with acute stroke in South India - S Revathi; M S Kavitha; V Shankar (Wolters Kluwer Medknow Publications, 2023)
Background: Early hospital presentation is critical in the management of acute ischemic stroke. The effectiveness of stroke treatment is highly dependent on the amount of time lapsed between onset of symptoms and treatment. This study was aimed to identify the factors associated with prehospital delay in patients with acute stroke. Material and Methods: A cross-sectional descriptive study was conducted in Sri Ramachandra University Hospital, India. A total of 210 patients hospitalized in the stroke unit were included. Patients' data were obtained by interviewing the patient and/or accompanying family member and by reviewing their medical records using a standard questionnaire. Associations were determined between prehospital delay (≥4.5 h) and variables of interest by using univariate and multivariate logistic regression analyses. Results: The prehospital delay was observed in 154 patients (73.3%) and the median prehospital delay was 11.30 h. The following are the factors significantly (P < 0.05) attributed for the delay in presenting to the hospital: contextual factors like using public transport (bus), taxi, time of onset of symptoms, 7 pm-3 am; family history of stroke, perceived cognitive and behavioral factors like, wishing or praying for the symptoms to subside on its own, hesitation to travel due to long distance, delay in arranging transport, and arranging money for admission and wasting time by shopping for general practitioners, nursing homes, and hospitals. The presence of stroke symptom, headache, significantly decreased the prehospital delay. Conclusions: Prehospital delay is high in South India and influenced by clinical, contextual, and cognitive/behavioral factors.